Hysteroscopic evaluation of menorrhagia and correlation with saline infusion sonography and histopathology of the endometrium - Padval, Rahul K. M.; Gulamali, Duraiya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: This study aimed to evaluate and compare the diagnostic utility of hysteroscopy and saline infusion sonography in patients presenting with abnormal uterine bleeding, using the International Federation of Gynaecology and obstetrics classification system. Methods: The study included 97 women with menorrhagia attending the department of obstetrics and gynaecology, R. D. Gardi Medical College, Ujjain, from September 2011 to February 2013. All the participants underwent hysteroscopy, saline infusion sonography (SIS), and endometrial histopathology. The sensitivity, specificity, positive predictive value, and negative predictive value of each diagnostic method was calculated and compared. Results: Both hysteroscopy and SIS demonstrated high sensitivity and specificity in detecting structural lesions from the PALM group of abnormal uterine bleeding (AUB) aetiologies. For endometrial polyps, hysteroscopy had a sensitivity of 89.47% with a specificity of 87.17%, while SIS had a sensitivity of 100% and specificity of 88.46% (p<0.01). For submucous fibroids, hysteroscopy had a sensitivity of 82.35% and specificity of 91.25%, while SIS had a sensitivity of 88.23% and specificity of 88.75% (p<0.01). However, neither method was as effective for endometrial hyperplasia and the COEIN group. Hysteroscopy-guided biopsy could improve the sensitivity and specificity of hysteroscopy in detecting endometrial hyperplasia. Conclusions: Hysteroscopy and SIS are valuable tools in the diagnosis and management of AUB, with both methods demonstrating significant efficacy in detecting structural lesions, such as endometrial polyps and submucous fibroids. Further research is needed to refine these techniques and determine their optimal use in clinical practice, especially for the detection of endometrial hyperplasia and conditions within the COEIN group.